Reproductive Rights and the State. - Haussman, Melissa (Reproductive rights and policy., 2013)
Reproductive Rights and the State: Getting the Birth Control, RU-486, and Morning-After Pills and the Gardasil Vaccine to the U.S. Market tackles a subject that remains controversial more than 60 years after ""the pill"" was approved for use in the United S.